Negative Immune Checkpoint Protein, VISTA, Regulates the CD4+ Treg Population During Sepsis Progression to Promote Acute Sepsis Recovery and Survival - Gray, Chyna C.; Biron-Girard, Bethany; Wakeley, Michelle E.; Chung, Chun-Shiang; Chen, Yaping; Quiles-Ramirez, Yael; Tolbert, Jessica D.; Ayala, Alfred (Frontiers in Immunology, 2022)
Sepsis is a systemic immune response to infection that is responsible for 35% of in-hospital deaths and over 24 billion dollars in annual treatment costs. Strategic targeting of non-redundant negative immune checkpoint protein pathways can cater therapeutics to the individual septic patient and improve prognosis. B7-CD28 superfamily member V-domain Immunoglobulin Suppressor of T cell Activation (VISTA) is an ideal candidate for strategic targeting in sepsis. We hypothesized that immune checkpoint regulator, VISTA, controls T-regulatory cells (Treg), in response to septic challenge, thus playing a protective role/reducing septic morbidity/mortality. Further, we investigated if changes in morbidity/mortality are due to a Treg-mediated effect during the acute response to septic challenge. To test this, we used the cecal ligation and puncture model as a proxy for polymicrobial sepsis and assessed the phenotype of CD4+ Tregs in VISTA-gene deficient (VISTA-/-) and wild-type mice. We also measured changes in survival, soluble indices of tissue injury, and circulating cytokines in the VISTA-/- and wild-type mice. We found that in wild-type mice, CD4+ Tregs exhibit a significant upregulation of VISTA which correlates with higher Treg abundance in the spleen and small intestine following septic insult. However, VISTA-/- mice have reduced Treg abundance in these compartments met with a higher expression of Foxp3, CTLA4, and CD25 compared to wild-type mice. VISTA-/- mice also have a significant survival deficit, higher levels of soluble indicators of liver injury (i.e., ALT, AST, bilirubin), and increased circulating proinflammatory cytokines (i.e., IL-6, IL-10, TNFα, IL-17F, IL-23, and MCP-1) following septic challenge. To elucidate the role of Tregs in VISTA-/- sepsis mortality, we adoptively transferred VISTA-expressing Tregs into VISTA-/- mice. This adoptive transfer rescued VISTA-/- survival to wild-type levels. Taken together, we propose a protective Treg-mediated role for VISTA by which inflammation-induced tissue injury is suppressed and improves survival in early-stage murine sepsis. Thus, enhancing VISTA expression or adoptively transferring VISTA+ Tregs in early-stage sepsis may provide a novel therapeutic approach to ameliorate inflammation-induced death.